2017
DOI: 10.3389/fendo.2017.00229
|View full text |Cite
|
Sign up to set email alerts
|

A Practical and Time-Efficient High-Intensity Interval Training Program Modifies Cardio-Metabolic Risk Factors in Adults with Risk Factors for Type II Diabetes

Abstract: IntroductionRegular physical activity (PA) can reduce the risk of developing type 2 diabetes, but adherence to time-orientated (150 min week−1 or more) PA guidelines is very poor. A practical and time-efficient PA regime that was equally efficacious at controlling risk factors for cardio-metabolic disease is one solution to this problem. Herein, we evaluate a new time-efficient and genuinely practical high-intensity interval training (HIT) protocol in men and women with pre-existing risk factors for type 2 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 46 publications
11
96
0
5
Order By: Relevance
“…A similar effect was observed with time‐averaging strategies. The difference between the 6‐b and 60‐b averaging strategies was reduced from 10.1% to 8.5% following a HIT training program that increased trueV˙O 2max by ~8% ( P < 0.05 and P < 0.001 for intercepts and slopes, respectively; n = 41). This effect was partially reverted following three weeks of detraining, that is, the difference between the 6‐b and 60‐b averaging strategy increased to 9.9% ( P = 0.35 and P = 0.03 for intercepts and slopes compared to pre‐training, respectively).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A similar effect was observed with time‐averaging strategies. The difference between the 6‐b and 60‐b averaging strategies was reduced from 10.1% to 8.5% following a HIT training program that increased trueV˙O 2max by ~8% ( P < 0.05 and P < 0.001 for intercepts and slopes, respectively; n = 41). This effect was partially reverted following three weeks of detraining, that is, the difference between the 6‐b and 60‐b averaging strategy increased to 9.9% ( P = 0.35 and P = 0.03 for intercepts and slopes compared to pre‐training, respectively).…”
Section: Resultsmentioning
confidence: 97%
“…Forty‐one subjects belonging to subgroups 1 and 2 participated in a 6‐week high‐intensity interval training (HIT) protocol aimed at increasing trueV˙O 2max . After the training period, a single trueV˙O 2max test was performed. This was followed by a 3‐week detraining period after which another single trueV˙O 2max test was performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some individuals show improvements with exercise training (eg, decrease in fasting glucose) and are considered responders , whereas others may not have such a response (eg, no change or even increases in fasting glucose) and are considered non‐responders . Individual variability has been reported mainly regarding fitness‐related variables, and in response to moderate‐intensity endurance (ET), resistance (RT), or high‐intensity interval training (HIT), and also in different age groups such as children, adults, or older populations, The existence of non‐responders for glucose homeostasis‐related variables has been confirmed more recently . In the present study, we confirmed a wide interindividual variability that is independent of the training‐induced changes after HIT, RT, or CT with regard to 20 outcomes and risk parameters, including 9 body composition, 3 cardiovascular, 3 metabolic, and 5 performance parameters.…”
Section: Perspectivesmentioning
confidence: 99%
“…The interindividual variability has been reported mainly in the context of fitness‐related variables, and in response to moderate‐intensity endurance (ET), resistance (RT), or high‐intensity interval training (HIT), and also in different age groups such as children, adults, or older populations . The existence of non‐responders for glucose homeostasis‐related variables has been confirmed more recently …”
Section: Introductionmentioning
confidence: 98%